2011
DOI: 10.9734/bmrj/2011/256
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Control of Bacterial Soft Rot Caused by Bacillus pumilus Od23 on Potato

Abstract: Potato soft rot, caused by Bacillus pumilus Od23, greatly affect potato tuber quality in storage and cultivars of Mali and indicated that it can affect all potato cultivars. Bacteria isolated from soil rhizosphere samples of healthy Malian indigenous trees were screened for their antagonistic effect against this pathogen. Three actinomycetes isolates (RoN, G1P, and N1F) were the most effective microbioagents in suppressing the growth of the pathogen. The biological control essay showed the possibility of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There are several species of Bacillus known as plant growth and health supporting in nature because of beneficial characteristic features which act directly and indirectly [2,3]. The principal mechanisms of plant growth promotion include: production of phytohormones such as indole acetic acid (IAA), solubilization of phosphate, siderophore production, antibiosis, inhibition of plant ethylene synthesis, production of volatile compounds such as HCN and induction of plant systemic resistance to pathogens [3][4][5]. One or more of these mechanisms may contribute to the increases obtained in plant growth and development that are higher than normal for plants grown under standard cultivation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There are several species of Bacillus known as plant growth and health supporting in nature because of beneficial characteristic features which act directly and indirectly [2,3]. The principal mechanisms of plant growth promotion include: production of phytohormones such as indole acetic acid (IAA), solubilization of phosphate, siderophore production, antibiosis, inhibition of plant ethylene synthesis, production of volatile compounds such as HCN and induction of plant systemic resistance to pathogens [3][4][5]. One or more of these mechanisms may contribute to the increases obtained in plant growth and development that are higher than normal for plants grown under standard cultivation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Their selected isolates were able to reduce rotting of potato tuber tissues by at least 50%. Babana et al (2011) confirmed that the soft rot disease in Malian potato tubers caused by Bacillus pumilus could biologically be controlled in potato slices by using the isolates of actinomycetes. Salem and Abd El-Shafea (2018) found, recently, that the severity disease was highly decreased under greenhouse conditions (in pots) by using various species (B. subtilis, P. fluorescens, P. aeruginosa, and Streptomyces spp.)…”
Section: Discussionmentioning
confidence: 57%
“…Recently, two novel Bacillus spp. were reported to cause soft rot of potato, B. altitudinis and B. pumilus (Babana et al, 2011;Elbanna, Elnaggar, & Bakeer, 2014). Similarly, Pseudomonas putida and Pseudomonas fluorescens were isolated from rotted potatoes (Muletet, Lalucat, & Garcia-Vades, 2010;Soleimani-Delfan, Etemadifar, Bouzari, and Emtiazi, 2012;Bhai, Kishore, Kumar, Anandaraj, & Eapan, 2012;Czajkowski, Boer, Veen, & Wolf, 2012).…”
mentioning
confidence: 99%